IMPROVING THE EDUCATIONAL PROCESS AND THE INFORMATION AND EDUCATIONAL AREA WITH THE USE OF "CLOUD TECHNOLOGIES" IN FORENSIC MEDICINE TEACHING (Modern education and development, 2025)
Cloud technologies (in English, cloud services, cloud technologies) are currently a broad term, the main content of which is the provision of certain types of software services using a program or software package not on the user's device, but on the service provider's device through the Internet.